THE ANALYSIS OF TRANSLATION METHODS AND PROCEDURES IN FACEBOOK :A Study Of Translation Methods And Procedures In Facebook Web Pages - ALLATIEF, Muhammad (2012)
This paper is entitled The Analysis of Translation Methods and Procedures in Facebook (A Study of Translation Methods and Procedures in Facebook Web Pages). The paper focused on two research questions. They were 1) which translation methods are used in translating 20 selected pages in Facebook website and, 2) which translation procedures are used in translating phrase in 20 selected pages in Facebook website. A descriptive qualitative method was applied.The findings exposed that there are five methods found in translating Facebook webpages. There are word-for-word method, faithful translation method, literal translation method, communicative translation method, and free translation method.The findings also exposed that there are eight translation procedures in translating Facebook webpages. The procedures are couplets, literal, shift, paraphrase, recognized translation, naturalization, through-translation, and reduction translation procedure.